Leminski: misturas e rarefações – entre te(n)sões e paixões - Tavares, Felipe de Almeida (2021)
Many of those who have worked on Leminski oeuvre recognize him as a writer capable of synthesizing antagonisms, with examples marked by the union of different artistic expressions or literary genres, of poetry and music, of popular culture and the erudite, of the East and West, among others. Considering this wide range of elements, the purpose of this work is to study the Leminskian poetry based on the thesis that his poems are composed through a practice we term as poetry of mixture and rarefaction, which results in wider intensity and extensity of the effects of his poetry. It is on this path, opened by the poetic sign, that Leminski finds his voice, a voice that, in search for the new and for the expressive freedom, affects varied readers, due to the fact that it articulates with different cultural aspects as it brings to the surface the particular effects of this poetry. One of the methodological approaches will be through the semiotic analysis of the poems, observing the effects and affects provided by this poetics, as well as its unfoldments. Including: the mixture of the senses through synesthesia; the mixture of words and their concepts; the breaking of aesthetic, cultural, media and even philosophical boundaries, creating a dialogue between different platforms and worldviews; the multiplicity of voices and the diminishing of the author’s voice (caused by the mixture and rarefaction of beings), lending more autonomy and spontaneity to the poetic text and a transformative subversion in opposition to the oppressive values, amid other important aspects for the appreciation of his style. As the central of our inquiry, we propose the reading of two books: Caprichos e relaxos and Distraídos Venceremos. Works which impacted the beginning and the end of his trajectory in life. As theoretical apparatus, considering the diversity of Leminskian mixtures, we approach interdisciplinarity in a certain way, combining the tensive semiotic by Fontanille and Zilberberg; the semantics and the philosophy, through authors such as Roland Barthes, dealing with his concept of pleasant and impertinent reading; Deleuze, especially regarding the mixture between beings and its resulting effects, as well as other names that enhance our understanding of this 1970’s generation poet, who is still today one of its most popular names.